PROBLEMS OF EDUCATION OF PEACE IDEAS IN HIGHER EDUCATION STUDENTS - Imamkulov Rasul Rakhmanovich (Scholar Express Journal, 2024)
The education of peace ideas in students of higher education organizations presents a multifaceted set of challenges that impede the effective dissemination and internalization of these critical values. This study explores the key problems associated with the integration of peace education into higher education curricula, focusing on issues such as curriculum design, pedagogical approaches, institutional support, and cultural contexts. It identifies the gaps between theoretical frameworks and practical applications, highlighting the resistance from various stakeholders, including educators, students, and policy makers. Additionally, the research examines the influence of societal attitudes and global political climates on the perception and reception of peace education. Through a comprehensive analysis, the study proposes strategic solutions to overcome these barriers, emphasizing the need for interdisciplinary approaches, inclusive policies, and enhanced collaboration among educational institutions globally. The findings aim to provide a roadmap for higher education organizations to foster a more peaceful and conscientious student body capable of contributing positively to society.
Keywords: peace education; higher education; curriculum design